Digital Monitoring Synergy: Transforming Early Childhood Education Collaboration through a Parent-Integrated Academic System - Lailatus Syahria; Siti Mu’arafah; Fetty Ernawati (Seulanga : Jurnal Pendidikan Anak, 2026)
Digital transformation in early childhood education (PAUD) institutions demands innovative public relations management that can strengthen communication and collaboration between schools and parents. A problem frequently identified in previous studies is the low intensity of communication, largely due to parents' limited time. This study aims to design the concept of Digital Monitoring Synergy as an innovation in early childhood education institutions public relations management by integrating parent communities into the academic information system (SIAKAD). This study employs a qualitative approach using a conceptual modelling method based on literature review. Data were obtained from journal articles, books, and relevant scientific documents. The data were analysed through the stages of problem identification, extraction of user needs based on previous research findings, and synthesis of these  needs into system feature designs. The results of the study produced a conceptual model of Digital Monitoring Synergy consisting of several key features: daily child reports, activity galleries, public relations announcements, parent response columns, parent communities, service partners, and security alarms.